Multicomponent Staff Training Intervention to Improve Residential Dementia Care (PROCUIDA-Demencia): A Mixed-Methods 2-Arm Cluster Randomized Controlled Pilot and Clinical Outcomes Study - Torres-Castro, Sara; Rabaneda-Bueno, Rubén; López-Ortega, Mariana; Gutiérrez-Robledo, Luis Miguel; Guzmán, Azucena (Journal of the American Medical Directors Association, 2022)
OBJECTIVES: To evaluate the feasibility outcomes of implementing a multicomponent staff training intervention (PROCUIDA-Demencia) to promote psychosocial interventions and reduce antipsychotic prescription in Mexican care homes and study its effect on staff's care experience and residents' quality of life. DESIGN: A mixed-methods 2-arm cluster randomized controlled pilot study of a 2-day staff training program with baseline, 12 weeks, and 24 weeks of the PROCUIDA-Demencia intervention vs treatment as usual (TAU). SETTING AND PARTICIPANTS: Eight care homes in Mexico City were selected, from which 55 residents and 126 staff were recruited. INTERVENTION: In situ staff training consisting of evidence-based manualized psychosocial interventions of person-centered activities, reminiscence therapy, doll therapy, psychomotor dance therapy, and antipsychotic prescription review. Fidelity to protocol was supervised once a week. METHODS: Cluster-level feasibility measures included views of staff, residents, and relatives on acceptability, satisfaction, adherence, and fidelity to the intervention. Staff outcome measures were Maslach Burnout Inventory (MBI), Approaches to Dementia Questionnaire, and Sense of Competence in Dementia Care Staff. Residents' outcome measures included Quality of Life-Alzheimer's Disease scale (QoL-AD), and Neuropsychiatric Inventory-Nursing Home Version (NPI-NH). Staff distress was measured using the NPI-NH occupational disturbance scale. Feasibility was elicited through a focus group, and hierarchical linear mixed effects models were used to assess the adjusted effects of the respective measures. RESULTS: Observed medical practice showed the prescription of at least 1 antipsychotic in 41% of participants in the intervention group. Overall, 39% of residents reported discontinuation, and 15% reduction of antipsychotics, following the 12-week medical review in parallel with psychosocial interventions. Clinical outcomes contributed positively to the reduction in baseline staff burden according to the MBI after the intervention [mean difference -8.9, 95% confidence interval (CI) -17.7, -0.1, P = .049] and to the reduction in severity and frequency of behavior as per NPI-NH in residents (mean difference -9.4, 95% CI -17.5, -1.3, P = .025). CONCLUSIONS AND IMPLICATIONS: PROCUIDA-Demencia is a feasible intervention for Mexican care homes. Results contribute to the Mexican Dementia Plan optimizing dementia care by supporting the need for staff training to implement psychosocial interventions prior to prescribing antipsychotic medication.
Keywords: staff training; psychosocial interventions; Surveys and Questionnaires; care homes; person-centered care; dementia; Nursing Homes; Humans; antipsychotics; demence; hodnocení výsledků zdravotní péče; Quality of Life; lidé; Mexico; kvalita života; průzkumy a dotazníky; Dementia; long-term care; Outcome Assessment, Health Care; pečovatelské domovy